Bentuk Komunikasi Karyawan Down Syndrome dalam Pelayanan Pelanggan di Kopi Kamu Kebayoran Jakarta Selatan (Studi Pada Karyawan Down Syndrome) - Muria Putriana; Wina Puspita Sari; Decency Ananda Sylphania; Farida Rizqi Ardilia Ningrum; Jihan Salzabilla Winata; Jasmine Nazwa Putri Eriesta; Marcella Zeilanti Ramadhan; Navira Sharen Assyifa; Nur Rahmah Oktafina; Safa Amanda Karenina (Ikatan Dosen Menulis, 2025)
This study aims to identify the forms of communication used by employees with Down Syndrome in customer service at Kopi Kamu Kebayoran, South Jakarta. The research uses a qualitative descriptive approach. Informants were selected using purposive sampling, and data were collected through observation, interviews, and documentation. Data validity was tested using source triangulation. The findings show that the dominant form of communication used is verbal communication, especially spoken, aligned with the training method provided to help employees understand instructions, such as greeting customers and taking orders. Reading and writing were not included due to cognitive limitations. Nonverbal communication was shown through spontaneous smiling and hand gestures during interactions. Convergence appeared when customers adjusted their behavior to ease communication. Divergence occurred due to the employees' limited ability to respond in complex ways. Overaccommodation was observed through customers' empathy, such as speaking more slowly or using gestures. These behaviors created a friendlier and more open communication environment, where both parties could understand each other despite different abilities, reflecting respectful communication that allows everyone to participate.